Effects of Web-Mediated Professional Development Resources on Teacher-Child Interactions in Pre-Kindergarten Classrooms - Pianta, Robert C. (Early Child Res Q, 2008)
As the workforce in state-funded pre-kindergarten programs continues to grow in the United States, the promise of these and other early education opportunities (e.g., Head Start) depends in large part on in-service professional development and training in key instructional and interaction skills. In this paper, we describe effects of MyTeachingPartner (MTP), a web-based system of professional development resources, that include video exemplars and web-mediated consultation on specific dimensions of interactions with children for 113 teachers in a state-funded pre-k program. Teachers assigned to receive on-line consultation and feedback targeted to their interactions showed significantly greater increases in independent ratings of the quality of interactions than did those only receiving access to a website with video clips. The positive effects of consultation were particularly evident in classrooms with higher proportions of children who experienced economic risks. Implications of these findings for models of professional development and widespread needs for teacher access and support are discussed in relation to the effectiveness of early education.